Increasing the uptake of Intermittent Preventive Treatment of malaria in pregnancy using Sulfadoxine-Pyrimethamine (IPTp-SP) through seasonal malaria chemoprevention channel delivery: protocol of a multicenter cluster randomized implementation trial in Mali and Burkina Faso - Kadiatou Koita; Joel D. Bognini; Efundem Agboraw; Mahamadou Dembélé; Seydou Yabré; Biébo Bihoun; Oumou Coulibaly; Hamidou Niangaly; Jean-Batiste N’Takpé; Maia Lesosky; Dario Scaramuzzi; Eve Worrall; et al. (BMC Public Health, 2024)
Abstract Background The uptake of Intermittent Preventive Treatment of malaria in pregnancy using Sulfadoxine-Pyrimethamine (IPTp-SP) remains unacceptably low, with more than two-thirds of pregnant women in sub-Saharan Africa still not accessing the three or more doses recommended by the World Health Organisation (WHO). In contrast, the coverage of Seasonal Malaria Chemoprevention (SMC), a more recent strategy recommended by the WHO for malaria prevention in children under five years living in Sahelian countries with seasonal transmission, including Mali and Burkina-Faso, is high (up to 90%). We hypothesized that IPTp-SP delivery to pregnant women through SMC alongside antenatal care (ANC) will increase IPTp-SP coverage, boost ANC attendance, and increase public health impact. This protocol describes the approach to assess acceptability, feasibility, effectiveness, and cost-effectiveness of the integrated strategy. Methods and analysis This is a multicentre, cluster-randomized, implementation trial of IPTp-SP delivery through ANC + SMC vs ANC alone in 40 health facilities and their catchment populations (20 clusters per arm). The intervention will consist of monthly administration of IPTp-SP through four monthly rounds of SMC during the malaria transmission season (July to October), for two consecutive years. Effectiveness of the strategy to increase coverage of three or more doses of IPTp-SP (IPTp3 +) will be assessed using household surveys and ANC exit interviews. Statistical analysis of IPT3 + and four or more ANC uptake will use a generalized linear mixed model. Feasibility and acceptability will be assessed through in-depth interviews and focus group discussions with health workers, pregnant women, and women with a child < 12 months. Discussion This multicentre cluster randomized implementation trial powered to detect a 45% and 22% increase in IPTp-SP3 + uptake in Mali and Burkina-Faso, respectively, will generate evidence on the feasibility, acceptability, effectiveness, and cost-effectiveness of IPTp-SP delivered through the ANC + SMC channel. The intervention is designed to facilitate scalability and translation into policy by leveraging existing resources, while strengthening local capacities in research, health, and community institutions. Findings will inform the local national malaria control policies. Trial registration Retrospectively registered on August 11th, 2022; registration # PACTR202208844472053. Protocol v4.0 dated September 04, 2023. Trail sponsor: University of Sciences Techniques and Technologies of Bamako (USTTB), Mali.